COMMUNITY PARTICIPATION IN THE CREATIVITY OF THEMATIC VILLAGE TOURISM DEVELOPMENT - Desnamita Desnamita; Sarojini Imran; Yustisia P. Mbulu (Journal of Tourism Destination and Attraction, 2020)
Community creativity and community participation are essential to maintain sustainable village tourism destinations by creating thematic attractions. For example, Pulo Geulis Village, in the city of Bogor, is in the process of developing a thematic village. The uniqueness of this village, the community, has created a joint artistic mural. This study aims to analyse the stages of community creativity and types of community participation in Kampung Pulo Geulis. The research method used in this study is qualitative by utilising primary and secondary data. Data collection methods used in this study were structured interviews and observation documentation. This study uses the interactive analysis model of Miles and Huberman, which collects data, reduces data, displays data, and draws or verifies conclusions by triangulating data. Results study indicate the stage of community creativity, passed formation creative ideas and the availability of space artistic activities. Kampung Pulo Geulis Community has involved in participating and implementing the benefits. Keywords: Urban Creativity, Community Participation, Thematic Villages